Reconnaissance for Radioactive Deposits in the Buckland-Kiwalik District, Candle Quadrangle, Seward Peninsula, Alaska - West, Walter S.; Matzko, John J. (Geological Survey (U.S.), 1952)
Report discussing the U.S. Geological Survey's investigation of radioactive mineral deposits found in the Buckland-Kiwalik district on the Seward Peninsula of Alaska. Uranothorianite, as well as other radioactive minerals, were discovered in the area.